Analysis of Learning Obstacle to Numeracy Ability Based on Mathematical Resilience of Elementary Students - Ade Fitriana; Samsul Maarif ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2022)
The difficulty felt by students in the learning process when students face a question and students feel difficulties in using their knowledge, we can say it to be a learning obstacle. Meanwhile, in learning, mathematical resilience can be said to be a positive attitude of students in the learning process. The relationship of mathematical resilience to mathematics learning will make students more interested and motivated in learning mathematics. This type of research is descriptive qualitative. This study studies and explores the characteristics of learning obstacles to numeracy ability based on students' mathematical resilience in geometry materials. The data collection techniques used are numeracy ability tests with geometry materials, student mathematical resilience questionnaires, and interviews. The subjects in this study were 24 students of class V B of SDN Mekarjaya 01. In this study, the data were analyzed by identifying the answers of 24 respondents to the numeracy ability test and mathematical resilience questionnaire that students had conducted. The result is that we can see some of the characteristics of learning barriers found in grade V students of SDN Mekarjaya 01, the characteristics of these learning barriers include difficulties and weaknesses in calculating, difficulties in transferring knowledge, and difficulties in understanding mathematical language. Looking at the characteristics of learning barriers, it is concluded that students have resilience in mathematics can affect students' attitudes in facing problems in learning mathematics.